A Systematic review of the association between emotional intelligence and suicidal ideation in the english and chinese literature - Zhou, Xiaochang; Khan, Aqeel; Yusof, Ibnatul Jalilah (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Throughout history, suicide has presented a significant public health concern on a worldwide scale. Many research investigations have highlighted the harmful connection between emotional intelligence and thoughts of suicide. However, no published articles have systematically reviewed relevant research in China. The objective of this paper is to examine and assess literature concerning the correlation between emotional intelligence and thoughts of suicide within the last ten years. The review includes sources in both English and Chinese languages. Chinese and English databases were queried using keywords such as emotional intelligence, emotional competence, suicidal ideation, and suicidal thoughts. Three reviewers conducted individual assessments of titles, abstracts, and complete texts according to predefined eligibility criteria. Data synthesis involved the extraction and analysis of research methodologies and outcomes. Sixteen studies that met the eligibility criteria were included in this systematic review. These studies, published between 2013 and 2022, demonstrated good methodological quality. The Wong and Law Emotional Intelligence Scale (WLEIS) and Emotional Intelligence Scale (EIS) were frequently employed in these articles, with several studies suggesting that an individual's ability to manage emotions was closely linked to suicidal ideation. Additionally, emotional cognition and others' emotional management abilities were predictive of suicidal ideation to some extent. The findings highlight a notably strong negative correlation between emotional intelligence and thoughts of suicide. This indicates that emotional intelligence could serve as a fundamental component for future investigations into interventions for suicidal ideation